A GENRE BASED APPROACH IN IMPROVING STUDENTS’ WRITING NARRATIVE TEXT - NA, Rohimah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2019)
This research investigates Genre-based Approach in improving the students’ writing narrative text. The aims of this study were to to find out the effects of the Genre-based Approach in teaching writing narrative text. In collecting data, the writer used instrument; it is writing text (pre-test and post-test). The population of the research was the eighth grade students’ of Junior High School Karangtengah Garut. The writer used a proportional random sampling, so there were 34 students as the sample (25%) of the population: 15 males and 19 females. This research a used quantitative method and the pre-experimantal design. Two variables in this research: the independent variable research was using Genre-based Approach in teaching narrative text, and dependent variable was using narrative text in improving the writing skill. The result of the research showed that tobserved was 13.96 and tcritical was 2.0423. The criteria of test; Ho was accepted if - tcritical ≤ tobserved ≤ tcritical so that it was concluded that null hypothesis (HO) was rejected and the alternative hypothesis (Ha) was accepted because the score was – 2.0423 ≤ 13.96 ≥ 2.0423; therefore, there was a significant effect of using Genre-based Approach in teaching writing narrative text and 76% of students writing narrative text using Genre-based Approach was improved